Costume of the Population of the Cimmerian Bosporos in the Hunnic Period - Michel Kazanski; Anna Vladimirovna Mastykovа (Античная древность и средние века)
The purpose of this work is to determine the main features and characteristics of the costume of the sedentary population of the Cimmerian Bosporos in the Hunnic Period (last third of the fourth to mid-fifth century). The elements of men’s costume comprise mostly of metal parts of belt sets and shoes. Women’s costume from the period features several traditions: Pontic, Germanic, and Ponto-Germanic. The Pontic tradition is typical of the presence of elements of women’s attire (earrings, necklaces, bracelets, metal appliques) with the absence of brooches, usual for the Germans. The costume of the Germanic tradition shows two paired brooches placed on the shoulders or in the pectoral area. The Ponto-Germanic costume includes both Germanic brooches and the elements of the Pontic costume. The main artifacts determining the specificity of the costume of the Cimmerian Bosporos from the Hunnic Period are some types of belt and shoe sets, brooches featuring the local tradition, metal appliques, metal wide-opening beads, necklaces with cone-shaped and lunular pendants, crescent-shaped or three-partite earrings, metal mirrors with a central loop, and bracelets with zoomorphic endings. The Bosporan costume from the Hunnic Period also contains other elements, which distribution area covers vast territories, so they cannot be considered typically Bosporan. Among these there are fly brooches, earrings with a multifaceted pendant on one ending, bracelets with widened ends, buckles with elongated tongues, and so on. Simultaneously, the artefacts typical of the Pontic / Bosporan costume also widely distributed in Europe during the Hunnic Period. All these factors supplied the Bosporan costume from the Great Migration Period with fully international character, typical of the sedentary population both on the territory of the Roman Empire and in the adjacent regions of the Barbaricum.